Combined nicotinamide riboside and magnesium-l-theanine protects against chronic stress-induced gut-liver injury by modulating NAD+ and metabolic pathways - Orhan, Cemal; Celik, Abdullah; Uulu, Nursultan Arapbai; Gonyon, Madison T.; Şahin, Nurhan; Tuzcu, Mehmet; Şahin, Kazım (Springer, 2025)
BackgroundChronic variable stress (CVS) has been associated with increased intestinal permeability and hepatic dysfunction, primarily through oxidative imbalance and metabolic dysregulation. This study evaluated the protective effects of nicotinamide riboside (NR) and magnesium-L-theanine (MgT) supplementation against CVS-induced intestinal and hepatic damage in rats.Methods and resultsA total of 28 rats were randomly divided into four groups: Control, MgT + NR, Stress, and Stress + MgT + NR. NR (600 mg/kg/day) and MgT (400 mg/kg/day) were administered orally throughout the experimental period. The CVS model includes unpredictable stress factors such as water deprivation, exposure to cold, cage turning, exposure to intermittent flashing lights, physical restraint, wet bedding, and social isolation. Each of these factors was applied randomly every day for 40 days. CVS exposure significantly elevated serum glucose, corticosterone, ACTH, triglycerides, ALT, and AST levels, while reducing insulin, magnesium, and hepatic NAD(+), NADPH, NAM, and NA concentrations. MgT + NR supplementation effectively reversed these changes. Moreover, it restored the hepatic expression of PPAR gamma, SIRT-1, GLUT2, and IRS-1, while downregulating the expression of FASN and SREBF1. In the jejunum, tight junction proteins (Claudin-1, Claudin-4, Occludin, ZO-1), mucin (MUC-2), glucose transporters (SGLT1, GLUT2), and nutrient carriers (PepT1, LAT2, EAAT3, FABP2, FATP4) were significantly improved with treatment. Histological analysis confirmed amelioration of CVS-induced liver steatosis and intestinal architectural damage.ConclusionThese findings suggest that combined NR and MgT supplementation mitigates stress-induced metabolic and structural alterations in the gut-liver axis, likely through the modulation of NAD(+) metabolism and barrier function, and may serve as a promising trace element-based strategy for managing stress-related metabolic disorders.
Keywords: Chronic variable stress; Nicotinamide riboside; Magnesium l-theanine; Liver; Gut